Can augmented reality boost students’ cognitive levels in geography? - Resyifa Qatrunnada Salsabila; Yusuf Suharto (Universitas Papua, 2025)
Understanding spatial relationships and human-environment interactions is an important aspect of geography, but many students still struggle to develop the cognitive skills to understand the concept. Augmented Reality (AR) provides an interactive learning experience for students, but previous studies generally have focused on lower-order cognitive skills. This study aims to examine the effect of AR on students' ability to understand (C2), apply (C3), and analyze (C4). This study used quasi-experimental with a posttest-only control group design. 71 tenth-grade students were selected as samples through purposive sampling. The test instrument comprised multiple-choice and essay-type questions across three cognitive levels. Data were analyzed using a non-parametric method, namely the Mann-Whitney U test. The analysis showed no significant difference between the experimental and control classes in the understanding (C2) and applying (C3) domains. However, there are variations in results on several indicators in these two domains, so AR shows the potential to improve students' understanding and application in certain aspects. In contrast, there was a significant difference in the analyzing domain (C4), with all indicators showing significant differences. Thus, AR can effectively support students' analytical skills, while its role in improving understanding and application needs further study.